Design of Earthquake Early Warning System Based on Internet of Thing. Issue 1 (April 2021) - Gunawan, G; Nasution, B B; Zarlis, M; Sari, Marliana; Lubis, AR; Solikhun,
Abstract: Earthquake Early Warning is needed to reduce casualties and material losses. In this research, a system of earthquake disaster early detection system with vibration sensor and fuzzy algorithm is designed that is run on a microcontroller. In this study, the results of vibration measurements are obtained which are posed by earthquake vibrations and simulated in real time. This tool still needs to be developed and further calibrated to get perfect results.